2015
DOI: 10.1371/journal.pone.0121286
|View full text |Cite
|
Sign up to set email alerts
|

Tenotomy or Tenodesis for the Long Head of Biceps Lesions in Shoulders: A Systematic Review and Meta-Analysis

Abstract: BackgroundBoth tenotomy and tenodesis have been widely used for the treatment of long head of biceps tendon (LHBT) lesions, but the optimal strategy remains considerably controversial. In this meta-analysis of published studies, we compared the results of the two procedures.MethodsA literature search that compared tenotomy with tenodesis was performed using MEDLINE, and Embase until August 2014. A total of 7 studies reporting data on 622 subjects were included. Study quality was evaluated using the PEDro criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 40 publications
5
53
2
1
Order By: Relevance
“…In recent years, most researchers have focused on the comparison between the curative effects of LHBT tenotomy and tenodesis. A large number of clinical comparative studies and meta-analyses have assessed the treatment of LHBT lesions combined with RCR with tenotomy and tenodesis (20)(21)(22)(23)(49)(50)(51)(52)(53). These studies indicated that the pain and function of the shoulder joint may be significantly improved by the two methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, most researchers have focused on the comparison between the curative effects of LHBT tenotomy and tenodesis. A large number of clinical comparative studies and meta-analyses have assessed the treatment of LHBT lesions combined with RCR with tenotomy and tenodesis (20)(21)(22)(23)(49)(50)(51)(52)(53). These studies indicated that the pain and function of the shoulder joint may be significantly improved by the two methods.…”
Section: Discussionmentioning
confidence: 99%
“…Oh et al (22) also observed that residual pain in the pectoral muscles following LHBT tenotomy is likely to occur. A meta-analysis by Ge et al (49), including 7 studies, suggested that LHBT tenodesis had a higher Constant score and lower incidence of upper arm spastic pain and Popeye sign deformity than simple tenotomy. Shang et al (50) included 10 high-quality studies in their meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Both techniques are commonly used in the clinical practice. A tenotomy is relatively simple and easy, but it is reported that cosmetic deformity and weakness of the biceps are likely to occur after surgery, while tenodesis requires longer operation time.…”
Section: Discussionmentioning
confidence: 99%
“…Favorable outcomes have been reported for both procedures, and no clinical studies have definitively demonstrated the superiority of either arthroscopic technique. 2,[5][6][7][8]14 Advocates of biceps tenodesis cite its ability to better maintain length and tension of the proximal LHBT, thereby potentially preserving elbow flexion and supination strength and decreasing the risk of cosmetic deformity or cramping pain. 2,3,9,10,14 Compared with LHBT tenodesis, arthroscopic tenotomy is a less technically demanding surgery, decreases operative time, and requires little postoperative rehabilitation, allowing patients to return to full activity sooner.…”
mentioning
confidence: 99%